Positive mental health in students of the Pre-University Center of the National University Major Of San Marcos - Velázquez, Carlos (2017)
The present study aims at the identification of Positive Mental Health in students of the Pre-University Center of the Universidad Nacional Mayor de San Marcos for which an accidental sample of 938 students of which 436 are male and 502 are female_ Adapting Positive Mental Evaluation Scale (EESMP), obtaining a validity between 268 to .649 and a reliability between, 637 to 791 The results indicate that there are differences as a function of sex in factors F2, F3 and F5_ As for the shift in which they study, differences are observed in F1, F2, F4 and F5. As far as the Educational Institution from which they come, there are no differences In the Professional Ares where they postulate there are differences in F1, F3 and F4; Sex there are no differences and the correlation between the factors show significant posítive and negative relationships between low. and moderate.